Modifications of Paroemia Invariants - Taliya F. Pecherskikh (Evropejskij Issledovatelʹ, 2013)
The phenomenon of modifications of paroemia invariants proves that language constantly changes and develops. The realization of communication need through the new evocative forms of expression is generality of the opposite linguistic phenomena of occasional variants of paroemia, aimed at the establishment of equilibrium in phraseology.